Mild phenotypes and proper supercomplex assembly in human cells carrying the homoplasmic m.15557G > A mutation in cytochrome b gene. Issue 1 (12th October 2017) - Iommarini, Luisa; Ghelli, Anna; Leone, Giulia; Tropeano, Concetta Valentina; Kurelac, Ivana; Amato, Laura Benedetta; Gasparre, Giuseppe; Porcelli, Anna Maria
Abstract: Respiratory complex III (CIII) is the first enzymatic bottleneck of the mitochondrial respiratory chain both in its native dimeric form and in supercomplexes. The mammalian CIII comprises 11 subunits among which cytochrome b is central in the catalytic core, where oxidation of ubiquinol occurs at the Qo site. The Qo‐ or PEWY‐motif of cytochrome b is the most conserved through species. Importantly, the highly conserved glutamate at position 271 (Glu271) has never been studied in higher eukaryotes so far and its role in the Q‐cycle remains debated. Here, we showed that the homoplasmic m.15557G > A/ MT‐CYB, which causes the p.Glu271Lys amino acid substitution predicted to dramatically affect CIII, induces a mild mitochondrial dysfunction in human transmitochondrial cybrids. Indeed, we found that the severity of such mutation is mitigated by the proper assembly of CIII into supercomplexes, which may favor an optimal substrate channeling and buffer superoxide production in vitro. Abstract : Mammalian respiratory complex III (CIII) comprises 11 subunits among which cytochrome b is central in the catalytic core, where oxidation of ubiquinol occurs at the Qo site. The Qo‐ or PEWY‐motif of cytochrome b is the most conserved through species. We here showed that the homoplasmic m.15557G > A/MT‐CYB, which causes the p.Glu271Lys amino acid substitution predicted to dramatically affect CIII, induces a mild mitochondrial dysfunction. The severity of such mutation is mitigated by the proper assembly of CIII into supercomplexes, which may favor an optimal substrate channeling and buffer superoxide production in vitro .